Which treatment is best for hepatic encephalopathy due to end‐stage liver disease?. Issue 5 (May 2017) - Null, Danette; Langevin, Jessica; Hagen, Jason
Abstract : EVIDENCE‐BASED ANSWER : Rifaximin is as effective as other antibiotics or oral disaccharides for improving hepatic encephalopathy with a better safety profile (SOR: A, meta‐analysis of RCTs). Combination therapy of rifaximin and lactulose is more effective for reversal of hepatic encephalopathy with less mortality than lactulose alone (SOR: B, RCT). Prophylactic use of rifaximin plus lactulose reduces hospitalizations for hepatic encephalopathy more than lactulose alone (SOR: B, RCT).